Assessing the quality of studies funded by the Israel National Institute for Health Policy Research, 2010–2020 - Dan Even; Moshe Leshno; Avi Porath (Israel Journal of Health Policy Research, 2025)
Abstract Background Research is the basis of advancement in health and wellbeing in modern societies. Our study aims to examine the funding policy of the Israel National Institute for Health Policy Research (NIHP), a national foundation responsible for assessing the impact of the national Health Insurance Law on health services in Israel. The study aims to evaluate the studies funded from 2010 to 2020, considering their publication in scientific literature and other channels that may influence decision-makers. We compare findings to a previous internal examination of studies funded by the NIHP during 1996–2014. Our paper presents an approach for measuring the impact of health policy research. Methods All 378 studies funded by NIHP during the specified years were identified. Objective data were gathered by investigating scientific literature across three datasets: Web of Science (WOS), PubMed, and Google Scholar, including journal impact factor, quarterly index, and citation metrics. Concurrently, a questionnaire was developed to collect additional and subjective data from principal investigators of the funded research projects. Results In the final sample of 364 studies funded by NIHP from 2010 to 2020, after 11 were cancelled, and 3 were duplicates. 436 publications were retrieved in peer-reviewed journals. The average time elapsed from funding to scientific publication was 4.65 years. Metric parameters for the top publications of 231 funded studies with at least one publication in peer-reviewed journals revealed an average journal impact factor of 5.97 points and an average of 7.82 citations according to WOS and 14 citations according to Google Scholar. A comparison to 459 funded studies from 1996 to 2014 found a twofold increase in the impact factor. Nearly half of the principal investigators reported some influence on policy processes in the questionnaires, and the majority of the studies were also reported in popular media outlets. Conclusions The study provides an overview of the quality and potential influence of studies funded by NIHP, dedicated to supporting research in the field of health policy in Israel. Some of the findings are supported by results from similar inquiries. Several recommendations are introduced to enhance the quality and impact of the funded studies.